Odpowiedzi

2009-09-29T22:06:58+02:00
1) x+2y=9
y-1=3x

x+2y=9
-3x+y=1/*(-2)

x+2y=9
6x-2y=-2

7x=7
x=1

1+2y=9
x=1

2y=8/:2
x=2

x=2
y=4

2)x-y=2
1/2x-1/4y=1

x-y=2/(-1/2)
1/2x-1/4y=1

1/4y=0
y=0

x-y=2
y=0

x=2
y=0

3)-x=2
2(3x+y+5)=-10

-x-y=2
6x+2y+10=-10

-x-y=2/*2
6x+2y=-20

-2x-2y=4
6x+2y=-20

4x=-16/;4
x=-4

-4-y=2
x=-4

x=-4
y=6
2009-09-29T22:09:37+02:00
A)x-y=9
y-1=3x

x-y=9
-3x+y=1
----------
-2x=10/:(-2)
x=-5

b)x-y=2/*(-1/2)
1/2x-1=1/4y

-1/2x+1/2y=1
1/2x-1/4y=1
-----------------
1/4y=1/:1/4
y=4

c)-x-y=2
2(3x+y+5)=-10

-x-y=2
6x+2y+5=-10

-x-y=2
6x+2y=-10-5

-x-y=2
6x+2y=-15

-x-y=2/*2
6x+2y=-15

-2x-2y=4
6x+2y=-15
------------
4x=-11/:4
x=-8 3/4
2009-09-30T00:06:10+02:00
A) x+2y=9
y-1=3x

x+2y=9
y=1+3x

x+2×(1+3x)=9
y=1+3x

x+2+6x=9
y=1+3x

7x=-7 /7
y=1+3x

x=-1
y=1+3×(-1)

x=-1
y=-2